Avaliação do coproduto siderúrgico KR como estabilizador para diferentes tipos de solo - Fardin, Henrique Delboni (2024)
Brazilian road transport sector is responsible for 65% of freight transportation and faces challenges, with only 12.4% of its road network paved. The research highlights the shortage of materials for paving, driving the study of the steel co-product KR (CP KR) as a soil stabilizer. As this residue demonstrates technical and environmental feasibility for use in pavements, the aim of the work was to evaluate the performance of the steel co-product type KR as a soil stabilizer for paving. Laboratory tests were conducted to evaluate the physical, mechanical, and mechanistic parameters of soils with different percentages of fines and related to results obtained by other authors. The study on CP-KR for paving revealed its potential in modifying the physical indices of soils and increasing mechanical strength. The greatest increases in strength occur in soils with 55% fines, while the Resilient Modulus increased more in less clayey soils, reaching a strength increase of 275%. The soils showed a significant reduction in plastic deformation, with an average decrease of 72%. The results demonstrated the potential of CP-KR as a soil stabilizer for the composition of road pavements